The Concept of Spontaneity and its Relationship with the Individual Characteristics of Personality - Trofimov, Andrii; Karamushka, Liudmyla; Andrushchenko, Tetiana; Zelenin, Vsevolod; Trofimova, Daria (International Journal of Criminology and Sociology, 2021)
In this article, the authors consider the concept of spontaneity and the relationship of this characteristic with such individual personality characteristics as locus of control, autonomy, tolerance to uncertainty, creativity, self-regulation, flexibility in communication and spontaneity itself. The authors conduct an experiment that allows to trace this relationship. The research involved 205 people between the ages of 18 and 40, including 125 people living in Ukraine and 80 people living and studying abroad. The Ukrainian study group consisted of 82 women and 43 men. The group of foreign researchers consisted of 52 women and 28 men. To study the impact on the spontaneity of the sociocultural experience of the individual, representatives of other communities aged 18–39 were involved. The sample of foreign respondents was divided into 4 groups: countries in Europe, countries in Asia and Africa, CIS countries and other countries in the world 80 people in total. In the study, the authors conclude that spontaneity does not exist separately from other personality characteristics, is not an independent personal property that develops according to its own laws, but is closely connected with many important personality formations and structures, and in order to understand how these connections function, it is not enough to investigate spontaneity separately from other personality traits.